AN ANALYSIS OF SURPRISE ADJECTIVES IN JANE AUSTEN’S PRIDE AND PREJUDICE - Khayrulla Toshkuvvatov (TARJIMASHUNOSLIK VA TILSHUNOSLIKNING DOLZARB MUAMMOLARI: ZAMONAVIY TENDENSIYALAR VA YONDASHUVLAR, 2025)
This article explores the use of surprise adjectives in Pride and Prejudice by analyzing their frequency and context. It focuses on five adjectives: surprised, astonished, bewildered, shocked, and startled – words that explicitly denote surprise or confusion. The aim is to quantify their occurrences and interpret their usage patterns in the novel’s dialogue and narration.